Tafsir Imamat 10:1-7: Studi Eksegetis atas Konsep Kekudusan Radikal Allah dalam Peristiwa Api Asing - Deventi Krislia Panggalo; Corina Tangdiombo; Rosalinda Samba’ Langi’; Mikael Randa Karaeng; Yulita Kombong (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
This study examines the concept of God’s holiness in Leviticus 10:1–7 through an exegetical approach to the event of the “strange fire” offered by Nadab and Abihu. The background of this research lies in the need to rediscover the true meaning of God’s holiness, which is often misunderstood in contemporary worship practices. The purpose of this study is to explore the theological meaning of the passage and its implications for faith and worship. The research uses a qualitative method based on literature study, focusing on historical, literary, and thematic analysis of the biblical text. The findings reveal that God’s holiness in this passage is absolute and cannot be violated without serious consequences. The action of Nadab and Abihu in offering unauthorized fire shows that worship is not only about sincere intention but also about obedience to God’s commands. The immediate divine judgment highlights that God’s holiness demands total reverence. Furthermore, this event serves as a warning for the community to maintain holiness in worship. In conclusion, God’s holiness in Leviticus 10:1–7 is radical and requires complete obedience from humanity. The implication of this study is the importance of cultivating reverence, discipline, and obedience in worship, ensuring that faith practices are aligned with God’s will rather than human preference.